2018
DOI: 10.3389/fmicb.2018.01820
|View full text |Cite
|
Sign up to set email alerts
|

Managing the Microbial Community of Marine Fish Larvae: A Holistic Perspective for Larviculture

Abstract: The availability of high-quality juveniles is a bottleneck in the farming of many marine fish species. Detrimental larvae-microbe interactions are a main reason for poor viability and quality in larval rearing. In this review, we explore the microbial community of fish larvae from an ecological and eco-physiological perspective, with the aim to develop the knowledge basis for microbial management. The larvae are exposed to a huge number of microbes from external and internal sources in intensive aquaculture, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
68
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(72 citation statements)
references
References 144 publications
4
68
0
Order By: Relevance
“…To our knowledge, this is the first report on the occurrence of antimicrobial-resistant bacteria in the live feeds that are most frequently used in marine fish larvae rearing, as most of the previous studies have attempted to reduce bacterial load in these cultures [19,[25][26][27][28][29] or characterize the bacterial species associated with the live feeds [7][8][9][10][11]13,15,16,18,19,43]. Our findings have demonstrated that live-feed cultures used in a Chilean commercial hatchery of red cusk eel have high levels of resistant bacteria in both untreated and treated live feeds, suggesting that the usage of florfenicol is not a necessary causal condition for the development and maintenance of elevated frequencies of florfenicol resistance.…”
Section: Discussionmentioning
confidence: 97%
“…To our knowledge, this is the first report on the occurrence of antimicrobial-resistant bacteria in the live feeds that are most frequently used in marine fish larvae rearing, as most of the previous studies have attempted to reduce bacterial load in these cultures [19,[25][26][27][28][29] or characterize the bacterial species associated with the live feeds [7][8][9][10][11]13,15,16,18,19,43]. Our findings have demonstrated that live-feed cultures used in a Chilean commercial hatchery of red cusk eel have high levels of resistant bacteria in both untreated and treated live feeds, suggesting that the usage of florfenicol is not a necessary causal condition for the development and maintenance of elevated frequencies of florfenicol resistance.…”
Section: Discussionmentioning
confidence: 97%
“…In addition to interactions ongoing within the rearing tank, various inputs and losses from the tank also affect this microbe dominated food web. Figure from Vadstein et al (2018) .…”
Section: An Analysis Of the Problem And A Hypothesis For Dysbiosis: Amentioning
confidence: 99%
“…The species composition of the bacterial community of the system is determined by (1) the composition of the bacteria in the external sources mentioned above, and (2) the growth potential and the selective forces acting on the microbial community within the system. The growth within the system (header tanks, tubes, and rearing tanks) can be substantial, and may contribute with 10 8 bacteria L -1 h -1 ( Attramadal et al, 2014 ; Vadstein et al, 2018 ). Depending on the rearing conditions, this is 1.2–14 times higher than the bacteria brought in with the incoming water.…”
Section: An Analysis Of the Problem And A Hypothesis For Dysbiosis: Amentioning
confidence: 99%
See 1 more Smart Citation
“…Ocean net pen fish generally had lower microbial diversity than indoor reared fish for all fish body sites, but was most pronounced in the gill. This further suggests that the mucosal, even in adult fish that are least susceptible to BE impacts, has a high capacity to change which is critical when considering time scales for probiotic effects [27,79,80]. Probiotic treatments in fish are common but little is known about dosage for a given treatment along with frequency of administration for having a lasting effect.…”
Section: Discussionmentioning
confidence: 99%